THE INFLUENCE OF VARIETY FEATURES OF WINTER WHEAT GRAIN ON THE QUALITY OF BAKERY PROPERTIES - Barabolia, O. V.; Tatarko, Yu. V.; Antonovskiy, O. V. (Scientific Progress & Innovations, 2020)
The urgency of implementing a comprehensive objective assessment of a number of grain and flour qual- ity indicators was substantiated in the article, as whole-grain bread and bakery products are gaining popu- larity in the world, because the nutritional value of such products is much higher than those made from re- fined flour,. However, in recent years, Ukrainian bakery enterprises have been receiving flour with a low gluten content, which significantly decreases its baking properties. The purpose of the study was to deter- mine the quality of flour obtained from soft winter wheat grain and to identify differences depending on the variety, to investigate and establish the characteristics of flour, their impact on baking properties. 9 samples of soft winter wheat grain harvested in 2018–2019, developed and grown by breeders of Poltava State Agrarian Academy were chosen. The following winter wheat varieties were studied: Orzhytsia, Zelenyi Hai, Liutenka, Ariivka, Dykanka, Tsarychanka, Karmeliuk, Poltavchanka and Sahaidak. Physical and chemical properties of grain and flour obtained from it were carried out on hardness, protein and gluten content in flour, gluten quality, and bread volume. Also, the assessment of bread quality on such indicators as elastici- ty, color, taste, flavor, was determined in the laboratory of Poltava State Agrarian Academy certified by State Committee of Ukraine for Technical Regulation and Consumer Policy. In the study of the above men- tioned parameters we used conventional techniques, which correspond to National Standards of Ukraine. The process of baking bread samples consisted of several stages: preparation and dosing of raw materials, dough batching, fermenting, forming, processing, recovering, baking, and cooling. After analyzing baked bread, it has been found that all samples have a satisfactory quality score. The best overall score belongs to Poltavchanka winter wheat variety (5 points out of 5 possible according to generally accepted standards). Bread baked from flour of Ariivka winter wheat variety has a cracked rind crust surface (2 points), a semi- oval shape (3 points), and a light brown color (4 points). The crumb is low elastic, restores shape well (4 points), has a moderately big, uniform sparseness (3 points), is light in color with a gray shade (3 points), it has a specific flavor of wheat bread (4 points). The identified research results provide an opportunity to understand what baking products will be and to what it is necessary to pay attention to in order to improve the quality of bakery products and increase productivity.